Prevalence of Leishmania infection in three communities of Oti Region, Ghana. - Richard Akuffo; Michael Wilson; Bismark Sarfo; Naiki Attram; Mba-Tihssommah Mosore; Clara Yeboah; Israel Cruz; Jose-Antonio Ruiz-Postigo; Daniel Boakye; Javier Moreno; Francis Anto (PLoS Neglected Tropical Diseases, 2021)
Background Leishmaniasis is a neglected tropical disease caused by parasites of the genus Leishmania and is transmitted by various species of female phlebotomine sand flies. The first report of cutaneous leishmaniasis (CL) in Ghana refer to a cluster of cases in 1999-2003 in the Ho municipality of the Volta Region. We conducted an epidemiological assessment in the Oti Region, encouraged by recent reports of potential cases of CL. Methodology/principal findings Using a cross-sectional study design, the exposure to Leishmania was investigated in three communities of the Oti Region based on the leishmanin skin test (LST). LST results for 3,071 participants comprising 1091, 848, and 1132 persons from the communities of Ashiabre, Keri, and Sibi Hilltop, indicated an overall prevalence of exposure to Leishmania infection of 41.8% and individual community prevalence of 39.4%, 55.1%, and 34.2% respectively. Being male [AOR = 1.27; CI: 1.09, 1.49], and living in Keri [AOR = 1.83; CI: 1.43, 2.34] were associated with an increase in the odds of exposure to Leishmania. Being 5-10 years old [AOR = 1.48; CI: 1.06, 2.05], 11-17 years old [AOR = 2.03; CI: 1.45, 2.85], 18-40 years old [AORR = 2.83; CI: 1.81, 4.43] and 41-65 years old [AOR = 5.08; CI: 2.98, 8.68] were also significantly associated with increased odds of being exposed to Leishmania. Conclusions/significance This study demonstrated exposure to Leishmania in the study communities and also identified associated factors. Future efforts aimed at reducing exposure to Leishmania infection in the study area should take the associated factors into consideration.